Determinants of Indigenous Rights Adoption in Latin America: Political Implications and Incrementalism 1960-2016 - (:unkn) unknown (My University, 2023)
Broadly, this work asks: what leads to the varied political status of indigenous populations in Latin America? From a uniform point of political exclusion, in recent decades governments in the region have adopted various degrees of constitutional reforms to protect their original populations. Some indigenous populations in Latin America remain unrecognized, like those in Chile. Others have gained some recognition and access to equal democratic rights. In other countries, like Bolivia, indigenous peoples have the potential to gain constitutional autonomy and regional self-government for their communities. First, I argue that the rights expansion process depends partially upon the content of the provision to be adopted. Constitutional laws have different political implications for indigenous and non-indigenous groups based on their substantive content. The changes created in these constitutional revisions must be considered when examining the rights adoption process. Second, key domestic factors impact rights adoption, dependent on the political implications of the rights up for adoption. This dissertation finds an incremental nature to rights expansion. First, rights recognize previously excluded indigenous populations as political citizens, then move to equalize political representation for these groups. Next, adoptions go on to establish rights that correct historic economic and social inequalities suffered by indigenous communities. As the last step in constitutional rights adoption, states recognize indigenous regional autonomies and create new political institutions in their interest. I conduct a nested analysis to test the impact of domestic factors during the different phases on indigenous rights adoption in Latin America. Survival and firth logit models are first used to test regional patterns of domestic impacts on the rights adoption process, and the incremental nature of rights adoption. Democracy is found to not be associated with the extension of equal democratic constitutional representation to indigenous groups, contrary to conventional knowledge. After initial recognition is gained, indigenous mobilization positively predicts the adoption of indigenous representation, resource, and autonomy provisions. Additionally, indigenous representation in national government is positively related to the adoption of indigenous autonomy rights in the national constitution. Along with these results, other interesting conclusions are drawn from the domestic impacts on rights adoption. Survival and logit models also find support that indigenous constitutional rights expand in a step-by-step process. That is, first, constitutions create terms of equal political rights before going on to address indigenous issues and difference. Case study evidence supports theories of the incremental adoption of indigenous constitutional protection. Bolivia, the most successful case, has engaged in a strategy of incrementalism, while Chile has recently tried to make far-reaching indigenous adoptions in one revision, which failed to pass. State level analysis also reveals that democracy does tend to precede a political opening to political marginalized populations, but strong indigenous mobilization and national representation is key in procuring far reaching constitutional rights that protect indigenous land, resources, and sovereignty.
Keywords: Comparative Politics; Constitutional Law; Indigenous Studies; Latin American Politics; Rights